An innovative intermittent hypoxia model for cell cultures allowing fast Po2 oscillations with minimal gas consumption - Minoves, Mélanie; Morand, Jessica; Perriot, Frédéric; Chatard, Morgane; Gonthier, Brigitte; Lemarié, Emeline; Menut, Jean-Baptiste; Polak, Jan; Pépin, Jean-Louis; Godin-Ribuot, Diane; Briançon-Marjollet, Anne (American journal of physiology. Cell physiology, 2017)
Performing hypoxia-reoxygenation cycles in cell culture with a cycle duration accurately reflecting what occurs in obstructive sleep apnea (OSA) patients is a difficult but crucial technical challenge. Our goal was to develop a novel device to expose multiple cell culture dishes to intermittent hypoxia (IH) cycles relevant to OSA with limited gas consumption. With gas flows as low as 200 ml/min, our combination of plate holders with gas-permeable cultureware generates rapid normoxia-hypoxia cycles. Cycles alternating 1 min at 20% O2 followed by 1 min at 2% O2 resulted in Po2 values ranging from 124 to 44 mmHg. Extending hypoxic and normoxic phases to 10 min allowed Po2 variations from 120 to 25 mmHg. The volume of culture medium or the presence of cells only modestly affected the Po2 variations. In contrast, the nadir of the hypoxia phase increased when measured at different heights above the membrane. We validated the physiological relevance of this model by showing that hypoxia inducible factor-1α expression was significantly increased by IH exposure in human aortic endothelial cells, murine breast carcinoma (4T1) cells as well as in a blood-brain barrier model (2.5-, 1.5-, and 6-fold increases, respectively). In conclusion, we have established a new device to perform rapid intermittent hypoxia cycles in cell cultures, with minimal gas consumption and the possibility to expose several culture dishes simultaneously. This device will allow functional studies of the consequences of IH and deciphering of the molecular biology of IH at the cellular level using oxygen cycles that are clinically relevant to OSA.
Keywords: Culture Media; faktor 1 indukovatelný hypoxií - podjednotka alfa; nádorové buněčné linie; hypoxie; Breast Neoplasms; Hypoxia; mTOR complex 1; Blood-Brain Barrier; design vybavení; hypoxie buňky; Cell Culture Techniques; Time Factors; Gases; Hypoxia-Inducible Factor 1, alpha Subunit; plyny; Cell Line, Tumor; Tumor Hypoxia; Equipment Design; Sleep Apnea, Obstructive; kyslík; ženské pohlaví; nádorová hypoxie; zvířata; Humans; cell hypertrophy; microRNAs; endoteliální buňky; časové faktory; kultivační média; buněčné kultury; nádory prsu; fibrosis; obstrukční spánková apnoe; Oxygen; hematoencefalická bariéra; Cell Hypoxia; Female; diabetic nephropathy; lidé; Endothelial Cells; Animals